Metastable pitting corrosion behavior of the Incoloy 825 liner of metallurgically clad pipe in simulated oilfield produced water - Anqing Fu; Chunsheng Wu; Kai Li; Wensheng Li; Xuanpeng Li; Hang Su; Zihan Chen; Chengxian Yin; Zhengyi Xu (Journal of Materials Research and Technology)
This study investigates the metastable pitting corrosion behavior and passive film characteristics of metallurgically clad pipe (MCP) 825 within simulated oilfield produced water. Electrochemical testing and microstructural examination were employed to assess the corrosion behavior. The results revealed a narrowing of the passivation region and an increased frequency of metastable pitting nucleation. These phenomena are attributed to the enlarged grain size and the proliferation of precipitate phases within the MCP 825. X-ray photoelectron spectroscopy analysis unveiled a decreased fraction of Cr3+ and Fe3+ ox in the passive film. Additionally, an elevated concentration of vacancies and a rapid vacancy diffusion rate were observed, leading to diminished defect performance as indicated by Mott-Schottky (M − S) and electrochemical impedance spectroscopy (EIS) results.